2018
DOI: 10.1177/1024258918762963
|View full text |Cite
|
Sign up to set email alerts
|

Social protests, discontent and politics in southern and eastern Europe

Abstract: Taking into consideration the debate on the role of social movements and of trade unions in organising social protests, in the light of contentious and conventional politics, this article examines participation in demonstrations in Europe and the political attitudes of the participants. The article uses data from the European Social Survey to examine the differences and similarities between European countries in respect of mobilisation levels over the past decade, arguing that distrust and dissatisfaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…This suggests a more moderate impact of the Great Recession and its associated reforms, compared to Portugal, and greater union resilience in general. However, the presence of unionists in the citizen demonstrations and protests was lower than that recorded in Portugal (Campos Lima and Martín Artiles, 2018: 212–213), and employee representation in companies has also been weakened, which is the centre of their power (Martínez Lucio, 2017: 91). The two large left-wing confederations accounted for 76% of union representatives in companies in 2007 (Sánchez-Mosquera, 2018: 29), while by 2019 their joint representation had fallen to 67.4%.…”
Section: Discussing the Importance Of Political Attitudes In Relation...mentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests a more moderate impact of the Great Recession and its associated reforms, compared to Portugal, and greater union resilience in general. However, the presence of unionists in the citizen demonstrations and protests was lower than that recorded in Portugal (Campos Lima and Martín Artiles, 2018: 212–213), and employee representation in companies has also been weakened, which is the centre of their power (Martínez Lucio, 2017: 91). The two large left-wing confederations accounted for 76% of union representatives in companies in 2007 (Sánchez-Mosquera, 2018: 29), while by 2019 their joint representation had fallen to 67.4%.…”
Section: Discussing the Importance Of Political Attitudes In Relation...mentioning
confidence: 96%
“…Left-wing attitudes, including far left, the defence of the public sector and the protection of jobs (Campos Lima and Martín Artiles, 2014) have been factors upon which these alliances have been formed, and which augment the strength and power of Portuguese unionism. In fact, this strong movement of spirited activism and the greater presence of unionists in these protests may well have favoured the arrival of a progressive government in 2015 (Campos Lima and Martín Artiles, 2018: 212). This government had success and proved to be durable against the odds and this evidently favoured left-wing confederal unionism.…”
Section: Discussing the Importance Of Political Attitudes In Relation...mentioning
confidence: 99%
“…Studies of the post-2008 cycle of contention in Southern Europe have shown how unions aligned with other social actors in organizing mass protests so their repertoire of contention expanded, rather than contracted (Accornero and Pinto, 2015; Portos and Carvalho, 2019). Organized labour makes its voice heard through collective bargaining, but workers also express their grievances by means of protests, demonstrations or petitions (Campos Lima and Artiles, 2018), or as Mathers et al (2018) argue, trade union deinstitutionalization has ‘opened up civil society as a terrain on which to remobilise trade unionism as a social movement’ (p. 14). As a result, the literature conceptualizes social movement unionism either as a union strategy of entering coalitions with civil society organizations and social movements, or as a strategy of employing a contentious action repertoire focused on protests and marches (Frege and Kelly, 2003, 2004; Hyman and Gumbrell-McCormick, 2017; Mathers et al, 2018).…”
Section: Union Strategies During the Great Recession: The Post-social...mentioning
confidence: 99%
“…Although differences between Croatia and Serbia should not be over accentuated, in the varieties of capitalism framework that Bohle and Greskovits (2012) developed to account for post-socialist diversity, Serbia is closer to the neoliberal model coupled with weak state institutions, while Croatia shares features of the embedded neoliberalism of the Visegrad group. Studies have shown that in neoliberal economies where unions are fragmented, competitive and without regular access to policy-making, they tend to rely more on protest activities and movement-like strategies (Campos Lima and Artiles, 2018; Gentile and Tarrow, 2009). In such contexts, it is also more likely that workers align with social movements and choose confrontational modes of expression (Vandaele, 2016).…”
Section: Union Strategies During the Great Recession: The Post-social...mentioning
confidence: 99%